Sarcoptic mange in Felidae: does Sarcoptes scabiei var. felis exist? A first molecular study. - Moroni, Barbara; Albanese, Francesco; Rita Molinar Min, Anna; Pasquetti, Mario; Guillot, Jacques; Pisano, Simone Roberto Rolando; Ryser-Degiorgis, Marie-Pierre; Rüfenacht, Silvia; Gauthier, Dominique; Cano-Terriza, David; Scaravelli, Dino; Rossi, Luca; et al. (Parasite, 2023)
Domestic and wild felids are considered suitable hosts for the parasitic mite Sarcoptes scabiei, and sarcoptic mange is reported in several felid species in the scientific literature. However, the historic classification of Sarcoptes mites into host-specific varieties does not include S. scabiei var. felis. It is unclear whether sarcoptic mange transmission in felids involves canids, other sympatric species, or exclusively felids. This study aimed to characterize the genetic structure of S. scabiei mites from domestic cats (Felis catus) and Eurasian lynx (Lynx lynx carpathicus), comparing them with Sarcoptes mites from sympatric domestic and wild carnivores. Ten Sarcoptes microsatellite markers were used to genotype 81 mites obtained from skin scrapings of 36 carnivores: 4 domestic cats, one dog (Canis lupus familiaris), 4 Eurasian lynx, 23 red foxes (Vulpes vulpes), and 4 grey wolves (Canis lupus lupus) from either Italy, Switzerland or France. Two genetic clusters of S. scabiei with a geographical distribution pattern were detected: mites from cats originating from Central Italy clustered with those from sympatric wolves. In contrast, all the other mites from Switzerland, France and Northern Italy clustered together. These results strengthen the previously advanced hypothesis that genetic variants of S. scabiei have a predominant geographic-related distribution with cryptic transmission patterns. These patterns may rely on the interactions between different hosts living in the same ecological niche rather than a simple infection among hosts belonging to the same taxon, reinforcing the idea that the S. scabiei historic classification into "var" might have little ongoing relevance.